The Heritage-scape: Origins, Theoretical Interventions, and Critical Reception of a Model for Understanding UNESCO’s World Heritage Program - Michael A. Di Giovine (Via@)
Written by the author of The Heritage-scape: UNESCO, World Heritage and Tourism (Lexington 2009), this article is a critical reflection of the heritage-scape concept nearly a decade after it was introduced in the literature. Including personal background stories that paint a picture of the intellectual origins and inspirations for the term, the article discusses the theory behind the heritage-scape, the concept’s contribution to the literature, and its reception by tourism and heritage theorists. As a theoretical buzzword meant to describe a particular, utopian model of the geopolitical order, it has nevertheless taken on a life of its own, and the article addresses some of the misconceptions, as well as clarifications made by the author, during the course of the last decade. Articulating a more holistic model of a World Heritage Program, the author also presents future areas of research — including more scholarship on the interrelatedness of tourism and heritage, and better integration of sustainability and ethics. The article concludes with a note of encouragement for junior scholars, who like the author a decade ago, felt they have something notable to communicate to the academic world.